EFFECTIVENESS OF AUDIO-VISUAL MEDIA TOWARDS ATTITUDES OF WOMEN SEX WORKER IN THE VISUAL ACETIC ACID INSPECTION (IVA) EXAMINATION - SOLIHAH, ENENG; SUGIARSIH, UGI; MULYO, GURID PE (International Journal of Psychosocial Rehabilitation, 2020)
Background: Cervical cancer is a health problem for women throughout the world. It is transmitted through sexual contact; 75 percent of infections occur in women who have had sex. One group of women of childbearing age who have a high risk include women who frequently change partners in sexual intercourse. One alternative method of screening for cervical cancer is visual inspection with acetic acid outfits (IVA). Efforts to influence attitudes towards IVA tests are conducting health education with audio-visual media (video). Objective: to determine the effectiveness of audio- visual media on the attitude of women sex worker in an IVA examination. Method: the study used a Quasi-Experiment design with a Pretest-Posttest one Group Design. The population in this study was Female Sex Worker in Karawang with a total sample of 47 respondents who were chosen by simple random sampling. Analysis with independent t-test. Result: there is a significant difference in attitude between before and after treatment with audio-visual media (video) with p- value is 0.001. The mean attitude difference between the pre-test and post-test is 13.32. Conclusion: Health education with audio-visual (video) media is effective on the attitude of women sex worker in an IVA examination.